Move/step analysis of learners’ oral case presentations by medical undergraduate students - Mahmud, Nur Farah Fadhliah (2017)
An oral case presentation (OCP) is a clinical communication that is essential for medical students to share pertinent information about patients’ reasons of admission, diagnoses and managements with their medical lecturers in an academic medical setting. Vast sources of literature have paid much attention on the genre analysis of written academic medical discourse such as case reports and journal articles. However, studies on OCP in academic settings using the genre approach particularly move analysis have yet to be researched. In producing oral case presentations, medical students are unable to organize information on chief complaints up to plans and managements. There are varied sources of OCP guidelines proposed that the students refer to in producing their OCPs. The main aim of this study was to carry out a schematic structure analysis particularly to find out the presence and sequence of moves and steps in the OCPs. In addition, linguistic features were identified to determine the moves and steps in the OCPs. This study also looks at how medical lecturers develop their teaching strategies in moulding and shaping students’ OCP especially in constructing the schematic structure of the genre. Bhatia’s (1993) genre theory which focuses on textual patterning and involves move/step analysis, text patterning and lexical grammatical feature was applied in this study. In total, thirty OCPs from thirty students who were in third, fourth and fifth year of study were collected from six different medical specialties namely Imaging, Medicine, Obstetrics and Gynaecology, Paediatrics, Psychiatry and Surgery, in the medical faculty of a public university in Malaysia. Qualitative data analysis was done using ATLAS.ti software in order to find out the presence and sequence of moves and steps in OCPs. AntConc software was also utilised to find out the frequency of linguistic features in the OCPs.Findings of the study show that Move 1 (M1) of chief complaint and Move 2 (M2) of history of presenting illness were used extensively in all thirty OCPs while the least move that was used was Move 11 (M11) of assessment and plan. The data analysis also revealed thirteen new moves such as menstrual history and nutritional history which were subjected to specific medical specializations. However, two new moves were emerged in all medical specialties, namely, provisional diagnosis and differential diagnosis. Noun phrases (NP) were used comprehensively in all the OCPs to indicate how one move progresses to a different move such as “family history”, “menstrual history” and “physical examination.” This study contributes to the literature on medical discourse, specifically, English for Medical Purposes (EMP) by providing a more structured and coherent guideline in producing OCP for novices so that they can organize their thoughts and gather information to produce a good and meaningful OCP.